Antibacterial, anti-HIV-1 protease and cytotoxic activities of aqueous ethanolic extracts from Combretum adenogonium Steud. Ex A. Rich (Combretaceae) - Mushi Novatus F; Mbwambo Zakaria H; Innocent Ester; Tewtrakul Supinya (BMC, 2012)
Abstract Background Records have shown that Combretum adenogonium Steud. Ex A. Rich (Combretaceae) is used in traditional medicine systems of several tribes in Tanzania. This study focused on the investigation of antibacterial activity, anti-HIV-1 protease activity, toxicity properties and classes of phytochemicals in extracts from C. adenogonium Steud. Ex A. Rich (Combretaceae) to evaluate potential of these extracts for development as herbal remedies. Methods Dried plant material were ground to fine powder and extracted using 80% aqueous ethanol to afford root, leaf and stem bark extracts. The extracts were assayed for anti-HIV-1 protease activities, antibacterial activities using microdilution methods and cytotoxicity using brine shrimps lethality assay. Screening for major phytochemical classes was carried out using standard chemical tests. Results All extracts exhibited antibacterial activity to at least one of the test bacteria with MIC-values ranging from 0.31-5.0 mg/ml. Two extracts, namely, root and stem bark exhibited anti-HIV-1 PR activity with IC50 values of 24.7 and 26.5 μg/ml, respectively. Stem bark and leaf extracts showed mild toxicity with LC50 values of 65.768 μg/ml and 76.965 μg/ml, respectively, whereas roots were relatively non-toxic (LC50 = 110.042 μg/ml). Phytochemical screening of the extracts indicated presence of flavonoids, terpenoids, alkaloids, tannins, glycosides and saponins. Conclusion These results provide promising baseline information for the potential development of C. adenogonium extracts in treatment of bacterial and HIV/AIDS-related opportunistic infections.